Educação infantil em tempo integral e os critérios predominantes de matrícula nas capitais brasileiras - Neves, Kalinca Costa Pinto das (2021)
This study analyzes the use of selection criteria established as a priority condition for the access to enrollment in full-time early childhood education in Brazilian capitals. It aims to question the criteria developed for the access to full-time early childhood education in these capitals and their possible correlations with education as a public and subjective right. Methodologically, we opted to perform an exploratory study of a qualitative nature whose data collection was made through the analysis of official documents made available by the respective municipal Departments of Education and the bibliographic review. Considering the diversity of the criteria used in the selection process, we opted for the use of the software NVivo that organizes and incorporates the words in graphs according to their frequency in the text. The choice for the participation of Brazilian capitals in this study was made by considering the complexity of planning and implementing public policies in large urban centers. Although the organization and selection of data with such a large focus was one of the greatest challenges of this study, the extended participation enabled us to have an overview of the organization of enrollment in full-time early childhood education with representation of all five regions of the country. Throughout the study, we endeavored to understand how these capitals have organized the enrollment process in full-time childhood education, attempting to identify the possible existence of selection criteria in this process, as well as possible similarities and differences between them. In the research process, it was possible to notice that the offer between pre-school and kindergarten appears in a different way, and the use of criteria occurs more frequently in the kindergarten. We also identified that, given the shortage of vacancies to meet all demands manifested, the selection criteria are also applied in part-time early childhood education in most of the contexts analyzed. The emphasis of the criteria used is on social and economic aspects, mainly the bond between families and conditional cash transfer programs and the health conditions of children and their families. Given that full-time early childhood education is a type of service provided in early childhood education, as being the right of all children, provided in the Federal Constitution of 1988; in the Law on National Education Guidelines and Frameworks (LDB, 1996) and in the Curriculum Guidelines on Early Childhood Education (DCNEI, 2010) and that should occur without a selection requirement, I concluded that the full-time program, in the context of early childhood education, has been established, although paradoxically, an experience of acknowledging rights and protection for children and their families. And that, the use of selection criteria in the enrollment process identified in the Brazilian capitals expose the inability of the State to carry out early childhood education as a public and subjective right.